Система автоматичного моделювання та моніторингу в гетерогенних мережах бездротового збору данних - Дідук, Віталій; Куценко, Станіслав (Видавництво Національного університету «Львівська політехніка», 2009)
The features of application of different types of wireless technologies for data transmission are considerea in the article. The systematization of basic parameters is conducted, the basic criteria of technologies choice are defined. The example of program realization of the automatic planning LAN-topology and data transmission by ZigBee
Keywords: modeling; ZigBee-stack; data transmission; planing